Gas, tubes and flow. Issue 4 (April 2020) - Henderson, Mark A.; Runcie, Colin
Abstract: Optimizing the flow of both liquids and gases is crucial to many areas of anaesthetic and critical care practice. In this article, we describe the physical principles that govern the flow of gases and present scenarios from clinical practice to illustrate these concepts. The difference between laminar and turbulent flow is explained, along with the factors that determine the nature of the fluid flow. The Venturi effect, Bernoulli principle and Coanda effect are also described with reference to their clinical applications and their relevance to medical devices.